How Do Pandemics End? Two Decades of Recurrent Outbreak Risk Following the Main Waves - Max Schroeder; Spyridon Lazarakis; Rebecca Mancy; Konstantinos Angelopoulos (Center for Economic Studies and ifo Institute (CESifo), 2021)
The risk of recurrent outbreaks following the main waves of a pandemic has been acknowledged. We provide evidence of the scale and duration of this outbreak risk. We compile municipal public health records and use national data to model the stochastic process of mortality rates after the main pandemic waves of two historical pandemics across multiple locations. For the 1890-91 influenza pandemic in England and Wales, as well as the 1918-19 influenza pandemic in the US and eight major UK cities, we find elevated mortality risk that persists for nearly two decades. The generality of the findings suggests that, without modern means of intervention, post-pandemic outbreak risk is likely to persist for an extended period, as we demonstrate in an application to COVID-19.
Keywords: 330; pandemics; outbreak risk; influenza; Covid-19; archive data